Functional significance of germline EPAS1 variants. Issue 2 (February 2021) - Dwight, Trisha; Kim, Edward; Bastard, Karine; Benn, Diana E; Eisenhofer, Graeme; Richter, Susan; Mannelli, Massimo; Rapizzi, Elena; Prejbisz, Aleksander; Pęczkowska, Mariola; Pacak, Karel; Clifton-Bligh, Roderick
Abstract : Mosaic or somatic EPAS1 mutations are associated with a range of phenotypes including pheochromocytoma and/or paraganglioma (PPGL), polycythemia and somatostatinoma. The pathogenic potential of germline EPAS1 variants however is not well understood. We report a number of germline EPAS1 variants occurring in patients with PPGL, including a novel variant c.739C>A (p.Arg247Ser); a previously described variant c.1121T>A (p.Phe374Tyr); several rare variants, c.581A>G (p.His194Arg), c.2353C>A (p.Pro785Thr) and c.2365A>G (p.Ile789Val); a common variant c.2296A>C (p.Thr766Pro). We performed detailed functional studies to understand their pathogenic role in PPGL. In transient transfection studies, EPAS1 /HIF-2α p.Arg247Ser, p.Phe374Tyr and p.Pro785Thr were all stable in normoxia. In co-immunoprecipitation assays, only the novel variant p.Arg247Ser showed diminished interaction with pVHL. A direct interaction between HIF-2α Arg247 and pVHL was confirmed in structural models. Transactivation was assessed by means of a HRE-containing reporter gene in transiently transfected cells, and significantly higher reporter activity was only observed with EPAS1 /HIF-2α p.Phe374Tyr and p.Pro785Thr. In conclusion, three germline EPAS1 variants (c.739C>A (p.Arg247Ser), c.1121T>A (p.Phe374Tyr) and c.2353C>A (p.Pro785Thr)) all have some functional features in common with somatic activating mutations. Our findings suggest that these three germline variants are hypermorphic alleles that may act as modifiers to the expression of PPGLs.